Genetic Risk for Alcoholic Chronic Pancreatitis - Mariânges Zadrozny Gouvêa da Costa; Dulce Reis Guarita; Ono S; Denise Cerqueira Paranaguá‐Vezozzo; Guilherme Eduardo Gonçalves Felga; Martha Regina Arcon Pedroso; Marcelo Moreira Tavares de Souza; Paulo Dominguez Nasser; Camila da Silva Ferreira; Flair José Carrilho (2011)
In recent years many studies have examined the genetic predisposition to pancreatic diseases. Pancreatic disease of an alcoholic etiology was determined to be a multi-factorial disease, where environmental factors interact with the genetic profile of the individual. In this review we discuss the main results from studies examining the frequency of genetic mutations in alcoholic chronic pancreatitis.